Kelebihan Investasi Forex Online - Lihan Rini Puspo Wijaya (Jurnal Ilmiah ESAI, 2016)
The newest investment area of most people in Indonesia is forex. Forex works based on currencies. Meanwhile, currencies are important to most people around the world, whether they realize it or not, because currencies need to be exchanged in order to conduct foreign trade and business (Investopedia, 2016). Despite some advantages provided through online forex trading, there are a few investors who invest and trade forex. To discuss, at least, there are ten advantages in online forex trading. Keywords: investment, trading forex online, buy, sell